The prevalence of cigarette smoking, alcohol and drug use among second year medical students in Dokuz Eylül University - Akvardar, Yıldız; Aslan, Belgin; Ekici, Z. Betül; Öğün, Esma; Şimşek, Tuncer (Journal of Dependence, 2001)
Object: Doctors have influence on the health of the society by providing treatment and prevention of diseases and as being role models. The health status of an individual is due in part at least to his/her own lifestyle and behaviour. It is therefore of interest to examine the lifestyles of today’s medical students-tomorrow’s doctors, who will be involved in future health care. The aim of this study was to determine the extent of substance use and severity of alcohol use among second year medical students in Dokuz Eylul University. Method: Information about substance use was obtained from 121 (81.2% of the second year students) second year students by self administered questionnaire. CAGE screening test was used to determine the severity of alcohol use. Results: The study group included 121 students; 74 men, 47 women, mean age 20.6±1.28. Prevalence of cigarette smoking was 27.3%, alcohol use 47.9%. Among those who drank, risky alcohol use is 6.6%. 12.3% of students thought of using illegal drugs. 6.7% of students used illegal drugs at least once. Discussion: Substance use was lower in second year medical students except cigarette smoking according to western universities. But still the levels of substance use in this sample of medical students are a cause of concern. The findings suggest a need for a larger study across different universities and faculties so that appropriate arrangements for student education and health care can be made.